11y-10g-22=13

Simple and best practice solution for 11y-10g-22=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11y-10g-22=13 equation:


Simplifying
11y + -10g + -22 = 13

Reorder the terms:
-22 + -10g + 11y = 13

Solving
-22 + -10g + 11y = 13

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '22' to each side of the equation.
-22 + -10g + 22 + 11y = 13 + 22

Reorder the terms:
-22 + 22 + -10g + 11y = 13 + 22

Combine like terms: -22 + 22 = 0
0 + -10g + 11y = 13 + 22
-10g + 11y = 13 + 22

Combine like terms: 13 + 22 = 35
-10g + 11y = 35

Add '-11y' to each side of the equation.
-10g + 11y + -11y = 35 + -11y

Combine like terms: 11y + -11y = 0
-10g + 0 = 35 + -11y
-10g = 35 + -11y

Divide each side by '-10'.
g = -3.5 + 1.1y

Simplifying
g = -3.5 + 1.1y

See similar equations:

| 18+z=37 | | 14-7x=.245 | | Log(x)=6.2 | | (x+6)(x-6)=B | | 97/(1-.3) | | 14+7x=.245 | | 120/(1-.3) | | 8x-(5x-7)=25 | | 171.34=120/(1-m) | | 100=75/(1-m) | | -3m+11=-6+5+4m | | 2(3(4)-1)-3(4(4)+3)-6=5x-4(4x-1) | | 120/1-51.34 | | 171.34-120/1-m | | 12m+23=179 | | 2(3x-1)-3(4x+3)-6=5x-4(4x-1) | | -92+7b=13 | | 9y+3=6(y-7) | | 9/10/69 | | -6(x+4)+4x+7=7x+9 | | 47+13a=164 | | 4w-13=47 | | 25x+35y=6 | | 25x-78=72 | | 8(5s-12)-16(2s+7)=0 | | 5x-(x-3)=-21 | | d/8*-4=-6 | | 14x^2-17=0 | | 38=6(y+7)-8y | | 2x-19=73 | | 6n-27= | | 7x^2+5y=22 |

Equations solver categories